PERCEPTION OF THE NURSING IMAGE AMONG NURSING STUDENTS AT PHAM NGOC THACH UNIVERSITY OF MEDICINE (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the proportion of positive perceptions of nursing image and identify factors related to the perception of nursing image among nursing students at Pham Ngoc Thach University of Medicine.Subjects and methods: A cross-sectional study was conducted on 408 first- to fourth-year nursing students at Pham Ngoc Thach University of Medicine.Results: The rate of positive perception towards the nursing profession among students was 96,81%, with a mean perception score of 162,38 ± 15,89 points. Factors associated with students’ perception of the nursing profession included: academic year, in which third- and fourth-year students had significantly higher perceptions (p < 0,001); a good initial impression, with a mean perception score of 170,18 points (p < 0,001); and good adaptability, with the highest mean perception score of 172,58 points (p < 0,001). No significant association was found between gender and students’ level of perception (p > 0,05).Conclusion: The study recorded a very high rate of positive perception towards the nursing profession among students. Therefore, it is necessary to continue maintaining career orientation, as well as enhancing soft skills training and psychological support to help students adapt well to the academic and clinical environment right from the early years of the program.
Keywords: Perception, nursing image, initial impression, adaptability.